THE EVOLUTION OF DIGITAL TERMINOLOGY IN MODERN ENGLISH - Qurbonova Farangiz Makhmudovna (International Engineering Journal For Research & Development, 2022)
This article is devoted to the study of digital modern English terminology, analyzing the reasons for the emergence of "Digital English", the relevance and importance of the process of studying and systematizing digital terminology. It can serve as a scholarly work for professionals or anyone who uses economic and digital terminology or is involved in the preparation of didactic materials for teaching. Based on the scientific research of experts in the field of economics and linguistics, the authors highlight the concept of the digital term in English, its essence and features. From the point of view of lexicology, its semantic, structural and functional features are shown. The technique of translating the terms classified in English into digital terminology in Uzbek, the study of this topic remains particularly relevant in terms of the synergy of the scientific apparatus of economics, finance and linguistics.